Surface chemistry guidance in controllable neural stem cell differentiation to direct stem cell fate: future applications in building artificial neural networks - Dhowre, Hala Shakib (2018)
Cell instructive biointerfaces are versatile tools to mimic a natural cellular environment and control cell fate in vitro. The particular interest lies in combining information gained from surface and interface analysis tools with biological analysis to explore and understand fundamental processes such as neuronal stem cell differentiation at the biointerface. A major challenge in biointerface design is to mimic and study the complex interactions of the natural processes in the extracellular matrix (ECM) with artificially designed surfaces and interfaces. In the past, peptide surfaces have been used as ECM mimics, however, more research is required in this field to tune the properties of peptide surface to modulate the outcome of stem cell fate. The present work aims to address this challenge by designing new synthetic peptide surfaces with well controlled composition and functionality able to impart have control over the differentiation of neuronal stem cells with the ultimate goal to relate surface properties and stem cell response to understand and control how neuronal networks function. Compositionally well-defined surfaces of two short laminin peptide sequences, Arg-Gly-Asp (RGD) and Ile-Lys-Val-Ala-Val (IKVAV) were prepared of various ratios via the “grafting from” stepwise approach. The surface modification was confirmed with surface analysis techniques to indicate successful peptide functionalization. The neural progenitor stem cells (NPSCs) were set up from embryonic rat hippocampi (E18). Immunocytochemistry (ICC) observed cell viability and differentiation to specific NPSCs lineages for βIII-Tubulin and GFAP. The surface characterizing techniques of WCA, AFM, ToF-SIMS, and XPS validated the successful orthogonal functionalization of controllable peptides composition surfaces with the increase of RGD composition a relative decrease in the IKVAV composition was observed. The increase in the normalized total ion fragments of RGD in the ToF-SIMS measurements can be related linearly to the % area coverage of neurons versus astrocytes observed on the controllable peptide composition surfaces. Well-defined peptide surfaces were designed and successfully demonstrated that the amount of RGD peptide composition present on the surface influences cell adhesion, proliferation and differentiation to a desirable cell fate or controllable cell population (i.e. neurons and astrocytes).